Nano-modulators with the function of disrupting mitochondrial Ca2+ homeostasis and photothermal conversion for synergistic breast cancer therapy - Chenglong Wang; Tao Li; Zhen Wang; Yao Li; Yan Liu; Maochang Xu; Zongquan Zhang; Yiping Deng; Liang Cai; Chunxiang Zhang; Chunhong Li (Journal of Nanobiotechnology, 2023)
Abstract Breast cancer treatment has been a global puzzle, and apoptosis strategies based on mitochondrial Ca2+ overload have attracted extensive attention. However, various limitations of current Ca2+ nanogenerators make it difficult to maintain effective Ca2+ overload concentrations. Here, we constructed a multimodal Ca2+ nano-modulator that, for the first time, combined photothermal therapy (PTT) and mitochondrial Ca2+ overload strategies to inhibit tumor development. By crosslinking sodium alginate (SA) on the surface of calcium carbonate (CaCO3) nanoparticles encapsulating with Cur and ICG, we prepared a synergistic Ca2+ nano-regulator SA/Cur@CaCO3-ICG (SCCI). In vitro studies have shown that SCCI further enhanced photostability while preserving the optical properties of ICG. After uptake by tumor cells, SCCI can reduce mitochondrial membrane potential and down-regulate ATP production by producing large amounts of Ca2+ at low pH. Near-infrared light radiation (NIR) laser irradiation made the tumor cells heat up sharply, which not only accelerated the decomposition of CaCO3, but also produced large amounts of reactive oxygen species (ROS) followed by cell apoptosis. In vivo studies have revealed that the Ca2+ nano-regulators had excellent targeting, biocompatibility, and anti-tumor effects, which can significantly inhibit the proliferation of tumor cells and play a direct killing effect. These findings indicated that therapeutic strategies based on ionic interference and PTT had great therapeutic potential, providing new insights into antitumor therapy. Graphical Abstract